Analysis of Receivables Practices in Manufacturing Companies: A Case of Nepalese Pharmaceuticals Companies - Pokharel, Post Raj (Saptagandaki Journal, 2020)
This paper presents the results of the survey and analysis of receivable practices in Nepalese pharmaceuticals companies. The survey is based on the structured questionnaire completed by 209 pharmaceuticals executives of which 44 were under corporate level, 98 under business level and 67 at operational level. The major issues dealt in the survey are concerned with the application of credit control policy, application of credit customer grading form, application techniques used to grant credit, application of “best practice” tips for effective credit control and opinion on practice of credit limit. Survey results showed that pharmaceuticals companies have desired to establish credit control policy with continuous practice of using credit application to screen new customer and renew them yearly. However, the practice of average collection period was not satisfactory in the companies. The choice of “references” for grading credit customer and ratio analysis were evident to grant credit.